The new encyclopedia of science:reference and set index - . ([New York] : Oxford University Press, 2003)
Essays and illustrations provide basic knowledge about a variety of scientific topics.
1. Matter and energy / John O.E. Clark -- 2. Animals and plants / Jill Bailey and Mike Allaby -- 3. Chemistry in action / Nina Morgan and John O.E. Clark -- 4. Stars and atoms / Stuart Clark -- 5. Earth and other planets / Peter Cattermole and Stuart Clark -- 6. Ecology and environment / Sally Morgan and Mike Allaby -- 7. Computing / Tony Dodd and Mike Allaby -- 8. Evolution and genetics / Jill Bailey -- 9. Reference and set index.
Cover title.
Set editorial consultant: John Clark.
Keywords: Science -- Encyclopedias, Juvenile; Science -- Encyclopedias